The dynamic interaction between a magnetically levitated vehicle and a flexible track - Lawton, Alan (1988)
The only commercially operating magnetically levitated (maglev) transport system in the world is the link between Birmingham International Airport and the National Exhibition Centre. Comparative financial analysis for this route showed that the construction costs for both wheeled and maglev systems were similar and that the cost of the guideway accounted for over 70% of the total. In part this was because the guideway was elevated; a likely requirement for any future urban system. A substantial reduction in installation costs for a system of this nature can only be achieved by the use of cheap, lightweight and flexible guideways.